Managing Renewable Energy: The Romanian Practice - Ion Plumb; Andreea Zamfir (Revista de Management Comparat International)
There are several support systems used by the governments of the European Unions countries for the promotion of renewable energy. The aim of this study is to explore the Romanian managerial approach used to encourage the renewable energy generation and consumption. First part of the study is focused on revealing the variety of national support systems used within the European Union to encourage renewable energy, and furthermore, the second part of the study explains the Romanian approach. The paper provides a rational approach for finding solutions to the problems of renewable energy promotion in the European Union. The findings of this study may be the subject of managerial know-how international transfer and may be used as a starting point for further investigations on renewable energy endorsement.